Skills and Employability of Graduates: The Role of Skills Development Programs in District Swat - Ilyas, Muhammad; Ali, Sher (iRASD Journal of Economics, 2023)
This study examined the impact of skills on the graduate`s employability, with the potential moderating role of employability skills development program activities. Primary data collected through a self-administered questionnaire from randomly selected 580 graduates (those graduates who have completed their graduation during 2017 - 2022) of district Swat, Khyber Pakhtunkhwa, Pakistan was used for the empirical analysis. Descriptive statistics, unpaired t-test analysis, and OLS regression analysis confirmed the hypothesis that skills have a significant positive impact on the graduate`s employability on employed, unemployed and combined group of graduates. The results also confirmed the potential moderating role of employability skills development program activities in the process. The specific employability components like personal qualities, core skills, initiative & enterprise, and attitude & work ethics are also found significantly related to the graduate`s employability. The findings of the study suggest that higher education institutions should properly plan for employability skills development program activities during graduation and ensure the participation of the students in such activities. The study also suggests that proper mechanisms should be implemented in higher education institutions to trace the skill development of the graduates during their graduation. Finally, it is suggested that the post-graduation employability skills development programs should be market-oriented and based on employer`s requirements.